2021
DOI: 10.22141/2224-1507.9.2.2019.172122
|View full text |Cite
|
Sign up to set email alerts
|

Кальциноз При Системній Склеродермії: Поширеність, Клініка, Менеджмент, Ускладнення

Abstract: This literature review summarizes current data on the epi demiology, pathophysiology, diagnosis and treatment of calcinosis cutis in patients with systemic sclerosis (SSc). The article deals with the analysis of observational studies of the frequency of calcinosis in SSc and associated clinical features, molecular research of potential pathogenetic mechanisms, clinical cases describing new diagnostic approaches and methods for the treatment of calcinosis. Calcinosis cutis is the deposition of insoluble calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…2 Previous data from the Scleroderma Clinical Trials Consortium showed calcinosis to be most commonly associated with digital ulceration, osteoporosis, telangiectasias, and acroosteolysis, 3 as well as with anticentromere, anti-PM/Scl, and anticardiolipin antibodies. 3 While calcinotic accumulations typically occur at pressure sites, 1,4 here we present an unusual case of calcinosis affecting the spinal canal.…”
mentioning
confidence: 79%
“…2 Previous data from the Scleroderma Clinical Trials Consortium showed calcinosis to be most commonly associated with digital ulceration, osteoporosis, telangiectasias, and acroosteolysis, 3 as well as with anticentromere, anti-PM/Scl, and anticardiolipin antibodies. 3 While calcinotic accumulations typically occur at pressure sites, 1,4 here we present an unusual case of calcinosis affecting the spinal canal.…”
mentioning
confidence: 79%